2008
DOI: 10.1016/j.carbon.2007.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Tuning nitrogen functionalities in catalytically grown nitrogen-containing carbon nanotubes

Abstract: Nitrogen-containing carbon nanotubes (NCNT) were grown from acetonitrile, pyridine or N,N-dimethylformamide over a supported Fe-, Co-or Ni catalyst in the temperature range 823-1123 K. The physico-chemical properties of the obtained NCNT, such as the C/N ratio or the nitrogen type, were related to the synthesis parameters. It was found that the C/N ratio increased with increasing temperature which could be related to the thermodynamic stabilities of the metal-carbides and metal nitrides. Also the type of nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
168
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(187 citation statements)
references
References 66 publications
16
168
0
3
Order By: Relevance
“…Figure 1(b) presents the high resolution XPS of N1s spectrum of the NGNSs, in which the complex XPS N1s spectra could be fitted to four components of the binding energy, namely pyridine-type nitrogen atoms (398.2 eV), pyrrolic-type N doping (399.9 eV), graphite-type nitrogen atoms (401.2 eV), and pyridine N-oxide (402.1 eV), indicating that the nitrogen has been doped in NGNSs with multiple status [19,20]. XPS measurement further reveals the NGNSs have a C/N molar ratio of about 8.2, which is by large identical with the result based on element analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1(b) presents the high resolution XPS of N1s spectrum of the NGNSs, in which the complex XPS N1s spectra could be fitted to four components of the binding energy, namely pyridine-type nitrogen atoms (398.2 eV), pyrrolic-type N doping (399.9 eV), graphite-type nitrogen atoms (401.2 eV), and pyridine N-oxide (402.1 eV), indicating that the nitrogen has been doped in NGNSs with multiple status [19,20]. XPS measurement further reveals the NGNSs have a C/N molar ratio of about 8.2, which is by large identical with the result based on element analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that the concentration and the type of nitrogen depend on the synthesis temperature, gas flow rate, and nature of the catalyst as well as the type of nitrogen precursor. [14][15][16][17] The most common forms of embedded nitrogen discussed in the literature are graphitic, pyridinic and pyrrolic nitrogen. 1,[18][19][20] Graphitic nitrogen refers to a nitrogen atom with three carbon neighbours in a hexagonal lattice, if the nitrogen is two-fold coordinated similar to that is found in pyridine, it is called pyridinic, and three-fold coordinated nitrogen in a region of defective non-aromatic lattice is associated with pyrrolic nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…It confirms that the incorporation of nitrogen in carbon framework indeed improves the catalytic activity. The presence of lone pair electrons of nitrogen had been reported to improve the basicity [25] and to increase the local electron density of the carbon surface [26], which could modify the metal species. Although the signal/noise ratio in XPS spectra (Fig.…”
mentioning
confidence: 99%